Connecting the Nation A short thematic history of Australian civil aviation - Ashton, Paul (UTS ePRESS, 2017)
Aviation has played an important part in shaping Australia's culture and history through the course of the twentieth century. Australia embraced aviation from its earliest days, eagerly responding to its potential to cover a challenging country, to bring far-flung communities closer and to provide services that could not be delivered any other way. Add the romance of pioneer heroes, the vital role of aviation in wartime and the capacity to deliver aid to people in need in Australia and beyond, and it is clear why aviation is at the heart of Australia's recent history. This book aims to set out the major themes that characterise Australia's aviation history for a broad audience and to provide a foundation for a broader discussion, and for further research, about how aviation transformed Australia. Connecting the Nation is a vital and timely introduction to the history of civil aviation in Australia as we prepare for the centenary of civil aviation services in 2020.